2020
DOI: 10.1016/j.ijbiomac.2020.07.290
|View full text |Cite
|
Sign up to set email alerts
|

Expression and purification of the extracellular domain of wild-type humanRET and the dimeric oncogenic mutant C634R

Abstract: This is a repository copy of Expression and purification of the extracellular domain of wildtype humanRET and the dimeric oncogenic mutant C634R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The expression of correctly folded and functional human RET requires the use of mammalian expression systems and we previously reported that the addition of a cleavable C-terminal Fc tag facilitates the expression of RET C634R ECD in its dimeric form, mediated by an intermolecular C630-C630 disulfide bond ( 25 ). For this study, we further optimized the expression construct (see Experimental procedures for details) and were able to isolate dimeric RET C634R ECD in high homogeneity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The expression of correctly folded and functional human RET requires the use of mammalian expression systems and we previously reported that the addition of a cleavable C-terminal Fc tag facilitates the expression of RET C634R ECD in its dimeric form, mediated by an intermolecular C630-C630 disulfide bond ( 25 ). For this study, we further optimized the expression construct (see Experimental procedures for details) and were able to isolate dimeric RET C634R ECD in high homogeneity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together with the BN PAGE and SEC-MALS data, these results suggest that RET C634R ECD forms a complex with GDF15 and GFRAL in a stoichiometry of 4:4:4 that must exist in a different configuration from the RET WT ECD complex. Indeed, we measured that the affinity of RET C634R ECD for GDF15/GFRAL ( K d = 8.5 μM) is actually weaker than that of RET WT ECD ( K d = 3.2 μM) ( 25 ) ( Fig. S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations